Nitrogen Application and Oat’s Genotypes Influence Nutritional Aspects of Oats (Avena sativa L.) Grains at Milky and Mature Stage of Development - Kaur, Gurjeet; Goyal, Meenakshi (Indian Journal of Animal Nutrition, 2017)
The objective of this study was to investigate effect of applied nitrogen on fodder yield and nutritional composition of oats seed comprising four genotypes (OL-9, Kent, OL-10 and OL-125). Experiment consisted of four nitrogen treatments i.e. 0, 50, 7 It was found that N application increased (P<0.05) crude protein, non protein nitrogen, in vitro dry matter digestibility (IVDMD) and ash contents of seeds. However, acid detergent fibre (ADF), neutral detergent fibre (NDF), hemicellulose and ether extract contents decreased (P<0.05) with increase in N fertilization. The seeds at milky stage exhibited higher NPN, IVDMD and ether extract content but had lower crude protein, ash content, ADF and hemicellulose than mature stage. Hence, nitrogen application decreased ADF, NDF and hemicellulose content and increased crude protein and IVDMD level at both milky and mature stage of grains.